Chilean Papaya (Vasconcellea Pubescens a. Dc.) Residues as a Source of Bioactive Compounds: Chemical Composition, Antioxidant Capacity, and Antiglycation Effects - Echeverria-Morgado, J; Mitsi, C (Elsevier Ltd, 2024)
The Chilean papaya (Vasconcellea pubescens A.DC.) is a climacteric fruit that grows in the north and center of Chile. During its processing, residues formed mainly by mucilage and seeds are produced and mostly discarded, despite being a potential source of bioactive metabolites. This work aimed to apply untargeted metabolic analysis by HPLC-DAD-QToF to study the chemical composition of ethyl acetate and methanol extracts from Chilean papaya residues and evaluate their antioxidant and antiglycation capacities. Twenty-three metabolites were tentatively identified in papaya residues, including one carboxylic acid, one glycosylated hydroquinone, four flavan-3-ols, three proanthocyanidins, twelve glycosylated flavonols, one carbohydrate, and one alkaloid reported for the first time. The antioxidant capacity measured as the scavenging of DPPH• and ABTS•+ radicals was comparable with that of ascorbic acid. Chilean papaya extracts decreased fluorescent Advanced Glycation End (AGE) products and oxidative modifications in proteins induced by glucose. © 2024